THERMODYNAMIC PROPERTIES OF CALCIUM ZEOLITES-STILBITE AND STELLERITE - Kiseleva I.A.; Navrotsky A.; Bclitsky A.; Fursenko A.A. (My University, 2001)
The thermodynamic properties of natural stilbite and stellerite were determined by the methods of high-temperature Calvet calorimetry. The standard enthalpies of formation from oxides and elements are -232.0 ± 8.3 and -11 017.9 ± 10.9 kJ/mol, respectively for stilbite of the Ca1.01Na0.12A12.12Si6.88O 18 · 7.27H2O composition and -200.1 ± 7.5 and -10909.1 ± 10.9 kJ/mol, respectively for stellerite of the Ca1.02Al2.01Si6.98O18 · 7.04H2O composition. The enthalpy of dehydration at 298.15 K is 229.2 ± 7.4 kJ/mol for stilbite and 214.5 ± 2.2 kJ/mol for stellerite; these values correspond to an endothermic effect of -30 kJ/mol at the removal of one mole of water from the framework of zeolite. The enthalpy values obtained were extrapolated to the ideal stoichiometric compositions; all thermodynamic characteristics for stilbite and stellerite of theoretical compositions were calculated taking into account experimental data from the literature.